Finite element analysis of temperature and residual stress profiles of porous cubic Ti-6Al-4V titanium alloy by electron beam melting. (1st May 2020) - He, Xiaochun; Li, Yang; Bi, Yongjie; Liu, Xiaomei; Zhou, Bing; Zhang, Shangzhou; Li, Shujun
Abstract: The temperature and stress profiles of porous cubic Ti-6Al-4V titanium alloy grids by additive manufacturing via electron beam melting (EBM) based on finite element (FE) method were investigated. Three-dimensional FE models were developed to simulate the single-layer and five-layer girds under annular and lateral scanning. The results showed that the molten pool temperature in five-layer girds was higher than that in single-layer grids owing to the larger mass and higher heat capacity. More energies accumulated by the longer scanning time for annular path than lateral path led to the higher temperature and steeper temperature gradient. The thermal stress drastically fluctuated during EBM process and the residual stress decreased with the increase of powder layer where the largest stress appeared at the first layer along the build direction. The stress under lateral scanning was slightly larger but relatively more homogeneous distribution than those under annular scanning. The stress distribution showed anisotropy and the maximum Von Mises stress occurred around the central node. The stress profiles were explained by the temperature fields and grids structure.